Ответы и объяснения

  • Участник Знаний
2014-03-29T13:55:02+04:00
cos2x + sin2x = 1/2   / домножим на 2
2cos2x + 2sin2x - 1 = 0 
2(cos^2x - sin^2x) + 4sinxcosx - (sin^2x + cos^2x) =  0
2cos^2x - 2sin^2x + 4sinxcosx - sin^2x - cos^2x = 0 
- 3sin^2x + 4sinxcosx + cos^2x = 0 / делим на минус 1 
3sin^2x - 4sincosx - cos^2x = 0  / делим на cos^2x ≠ 0
3tg^2x - 4tgx - 1 = 0 
Замена tgx = t 
3t^2 - 4t - 1 = 0 
D = 16 + 12 = 28
t1 = ( 4 +2√7)/6 = (2 + √7)/3
t1 = ( 4 - 2√7)/6 = (2  -  √7)/3

x = arctg (2+√7)/3 + pik
x = arctg ( 2 -√7)/3 + pik